Empathy Deficits and Their Behavioral, Neuroanatomical, and Functional Connectivity Correlates in Smoked Cocaine Users - Garcia-Serrano, A (Elsevier Inc., 2021)
Reduced empathic abilities are frequently observed in drug abusers. These deficits may compromise interpersonal interactions and contribute to diminished social functioning. However, previous evidence regarding empathy and addiction is behaviorally unspecific and virtually null in terms of their brain structural or functional correlates. Moreover, no previous study has investigated how empathy is affected by drugs whose consumption is particularly characterized by counter-empathic behaviors. Here, we conducted the first assessment of neurocognitive correlates of empathy for pain in dependent users (predominantly men) of smoked cocaine (SC, coca paste, n = 37). We compared their performance in the empathy task with that of two groups matched in relevant demographic variables: 24 dependent users of insufflated cocaine hydrochloride (CC) and 21 healthy controls. In addition, we explored the structural anatomy and functional connectivity (FC) correlates of empathic impairments across groups. Our results showed that, compared to CC and controls, SC users exhibited a selective reduction of empathic concern for intentional harms. These impairments were associated with lower gray matter volumes in regions subserving social cognition (i.e., right inferior parietal lobule, supramarginal and angular gyri). Furthermore, reduced empathic concern correlated with FC within affective empathy and social cognition networks, which are also linked to cognitive changes reported in addiction (i.e., inferior frontal and orbital gyri, posterior insula, supplementary motor area, cingulate cortex). Our findings suggest that chronic consumption of SC may involve reduced empathic concern and relevant neuroanatomical and FC abnormalities, which, in turn, may result in social interaction dysfunction. These results can inform theoretical and applied developments in neuropsychopharmacology. © 2021 Elsevier Inc.